Fabrication of a halopyridine appended Co(II) based 1D coordination polymer for efficient charge transportation. (1st June 2021) - Naaz, Sanobar; Das, Pubali; Khan, Samim; Dutta, Basudeb; Maity, Suvendu; Ghosh, Prasanta; Ray, Partha Pratim; Mir, Mohammad Hedayetullah
Graphical abstract: A new halopyridine appended Co(II) based coordination polymer (CP), [Co(3-clpy)2 (fum)2 (H2 O)2 ]n (1) 3-clpy = 3-Chloropyridine and H2 fum = fumaric acid has been synthesized and characterized by elemental analysis and single crystal X-ray diffraction (SCXRD) technique. The carboxylate linker, H2 fum propagates to form of a one dimensional (1D) polymeric structure. The 1D chains are interconnected via hydrogen bonding interactions leading to 2D sheet. The 3-clpy ligands of one chain facilitate π⋯π stacking interactions with adjacent chain leading to 3D supramolecular assembly. Hirshfeld surface analysis has also been performed to check the non covalent interactions in the crystal packing. Compound 1 shows electrical conductivity and reveals Schottky barrier diode behavior. Abstract: A new halopyridine appended Co(II) based coordination polymer (CP), [Co(3-clpy)2 (fum)2 (H2 O)2 ]n (1 ) 3-clpy = 3-Chloropyridine and H2 fum = fumaric acid has been synthesized and characterized by elemental analysis and single crystal X-ray diffraction (SCXRD) technique. Compound 1 crystallizes in monoclinic space group P 21 / c . Herein, the ditopic linker H2 fum acts as bridging ligand in the formation of a one dimensional (1D) CP. The 1D chains are interconnected via hydrogen bonding interactions leading to 2D sheet. The 3-clpy ligands of one chain facilitate π⋯π stacking interactions with adjacent chain leading to 3D supramolecular assembly which generally promotes better charge transport in the material. Hirshfeld surface analysis has also been performed to check the non covalent interactions in the crystal packing. Interestingly, the compound 1 shows electrical conductivity and reveals Schottky barrier diode behavior.